Comparison of different treatment planning approaches for intensity-modulated proton therapy with simultaneous integrated boost for pancreatic cancer - Stefanowicz, Sarah; Stützer, Kristin; Zschaeck, Sebastian; Jakobi, Annika; Troost, Esther Gera Cornelia (Radiation oncology, 2018)
Background: Neoadjuvant radio(chemo)therapy of non-metastasized, borderline resectable or unresectable locally advanced pancreatic cancer is complex and prone to cause side-effects, e.g., in gastrointestinal organs. Intensity-modulated proton therapy (IMPT) enables a high conformity to the targets while simultaneously sparing the normal tissue such that dose-escalation strategies come within reach. In this in silico feasibility study, we compared four IMPT planning strategies including robust multi-field optimization (rMFO) and a simultaneous integrated boost (SIB) for dose-escalation in pancreatic cancer patients. Methods: For six pancreatic cancer patients referred for adjuvant or primary radiochemotherapy, four rMFO-IMPT-SIB treatment plans each, consisting of two or three (non-)coplanar beam arrangements, were optimized. Dose values for both targets, i.e., the elective clinical target volume [CTV, prescribed dose Dpres = 51Gy(RBE)] and the boost target [Dpres = 66Gy(RBE)], for the organs at risk as well as target conformity and homogeneity indexes, derived from the dose volume histograms, were statistically compared. Results: All treatment plans of each strategy fulfilled the prescribed doses to the targets (Dpres(GTV,CTV) = 100%, D95%,(GTV,CTV) ≥ 95%, D2%,(GTV,CTV) ≤ 107%). No significant differences for the conformity index were found (p > 0.05), however, treatment plans with a three non-coplanar beam strategy were most homogenous to both targets (p < 0.045). The median value of all dosimetric results of the large and small bowel as well as for the liver and the spinal cord met the dose constraints with all beam arrangements. Irrespective of the planning strategies, the dose constraint for the duodenum and stomach were not met. Using the three-beam arrangements, the dose to the left kidney could be significant decreased when compared to a two-beam strategy (p < 0.045). Conclusion: Based on our findings we recommend a three-beam configuration with at least one non-coplanar beam for dose-escalated SIB with rMFO-IMPT in advanced pancreatic cancer patients achieving a homogeneous dose distribution in the target while simultaneously minimizing the dose to the organs at risk. Further treatment planning studies on aspects of breathing and organ motion need to be performed. Electronic supplementary material - The online version of this article (10.1186/s13014-018-1165-0) contains supplementary material, which is available to authorized users.
Gesehen am 09.04.2020